2021
DOI: 10.1001/jamanetworkopen.2021.2823
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patients Reading Clinical Notes With Perception of Medication Adherence Among Persons With Serious Mental Illness

Abstract: This survey study examines how patients with a mental illness diagnosis who read at least 1 clinical note in the last year perceived its association with their medication adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 3 publications
(5 reference statements)
1
45
0
Order By: Relevance
“…66 A recent survey analysis found that persons with serious mental illnesses-defined as including major depression, bipolar disorders and schizophrenia disorders-were significantly more likely than other patients to report feeling in control of their medications, to understand adverse effects, and to report taking their medications, after accessing their notes. 67 Even while acknowledging that there may be occasions when some patients with mental illnesses may be upset, or confused by what they read, or that some patients may even be harmed by access, 25 26 this growing body of research indicates that the majority of mental health patients derive benefits from reading their clinical notes. When health organisations deny mental health patients access to resources-namely, their clinical notes-this constitutes a form of hermeneutic injustice since it may impede patients' capacity to understand their clinical condition and treatment plan, and potentially to improve their health outcome.…”
Section: Extended Essaymentioning
confidence: 99%
“…66 A recent survey analysis found that persons with serious mental illnesses-defined as including major depression, bipolar disorders and schizophrenia disorders-were significantly more likely than other patients to report feeling in control of their medications, to understand adverse effects, and to report taking their medications, after accessing their notes. 67 Even while acknowledging that there may be occasions when some patients with mental illnesses may be upset, or confused by what they read, or that some patients may even be harmed by access, 25 26 this growing body of research indicates that the majority of mental health patients derive benefits from reading their clinical notes. When health organisations deny mental health patients access to resources-namely, their clinical notes-this constitutes a form of hermeneutic injustice since it may impede patients' capacity to understand their clinical condition and treatment plan, and potentially to improve their health outcome.…”
Section: Extended Essaymentioning
confidence: 99%
“…In surveys, mental health clinicians worry that patients will become anxious, confused or upset by what they read; many also anticipate access will lead to increased work burdens [ 4 6 ]. Findings drawn predominantly from primary care suggest that mental health patients may derive benefits from accessing their clinical notes including feeling more in control of their care, better remembering their care plan, and better understanding the rationale for medications [ 7 , 8 ]. However, sharing mental health notes could present more challenges than in other clinical specialties.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Findings drawn predominantly from primary care suggest that mental health patients may derive benefits from accessing their clinical notes including feeling more in control of their care, better remembering their care plan, and better understanding the rationale for medications. [7,8] However, sharing mental health notes could present more challenges than in other clinical specialties. Currently, only a few pilot surveys have examined patients' experiences in specialized mental health settings, and while the results are encouraging, at least some patients reported feeling disrespected or judged by what they read.…”
Section: Introductionmentioning
confidence: 99%